PKHB1, a thrombospondin-1 peptide mimic, induces anti-tumor effect through immunogenic cell death induction in breast cancer cells - Kenny Misael Calvillo-Rodríguez; Rodolfo Mendoza-Reveles; Luis Gómez-Morales; Ashanti Concepción Uscanga-Palomeque; Philippe Karoyan; Ana Carolina Martínez-Torres; Cristina Rodríguez-Padilla (OncoImmunology, 2022)
Breast cancer is the most commonly diagnosed cancer and the leading cause of cancer death in women worldwide. Recent advances in the field of immuno-oncology demonstrate the beneficial immunostimulatory effects of the induction of immunogenic cell death (ICD). ICD increases tumor infiltration by T cells and is associated with improved prognosis in patients affected by triple negative breast cancer (TNBC) with residual disease. The aim of this study was to evaluate the antitumoral effect of PKHB1, a thrombospondin-1 peptide mimic, against breast cancer cells, and the immunogenicity of the cell death induced by PKHB1 in vitro, ex vivo, and in vivo. Our results showed that PKHB1 induces mitochondrial alterations, ROS production, intracellular Ca2+ accumulation, as well calcium-dependent cell death in breast cancer cells, including triple negative subtypes. PKHB1 has antitumor effect in vivo leading to a reduction of tumor volume and weight and promotes intratumoral CD8 + T cell infiltration. Furthermore, in vitro, PKHB1 induces calreticulin (CALR), HSP70, and HSP90 exposure and release of ATP and HMGB1. Additionally, the killed cells obtained after treatment with PKHB1 (PKHB1-KC) induced dendritic cell maturation, and T cell antitumor responses, ex vivo. Moreover, PKHB1-KC in vivo were able to induce an antitumor response against breast cancer cells in a prophylactic application, whereas in a therapeutic setting, PKHB1-KC induced tumor regression; both applications induced a long-term antitumor response. Altogether our data shows that PKHB1, a thrombospondin-1 peptide mimic, has in vivo antitumor effect and induce immune system activation through immunogenic cell death induction in breast cancer cells.